Technology Assessment in Austria – a tentative attempt. (4th August 2014) - Peissl, Walter
Technology Assessment is an information tool for politicians and others, who are responsible decision makers in technological fields. To make sure that the scientific output is usable input for the decision makers you have to have in mind the specific political framework of each country. In the paper the specific Austrian relationship between Parliament and the strong corporatist structures – well known as 'Sozialpartnerschaft' – and their impacts on the development and institutionalization of TA in Austria, will be discussed. In the beginning there is a view on the development of TA in Austria to the present time. This is followed by an outlook on short–term developments and a possible model for TA in Austria. In the conclusion the fundamentals of the political system of Austria are described.